Lateralized Subthalamic Stimulation for Axial Dysfunction in Parkinson's Disease: A Randomized Trial. Issue 5 (13th February 2022) - Lizárraga, Karlo J.; Gnanamanogaran, Bhairavei; Al‐Ozzi, Tameem M.; Cohn, Melanie; Tomlinson, George; Boutet, Alexandre; Elias, Gavin J.B.; Germann, Jürgen; Soh, Derrick; Kalia, Suneil K.; Hodaie, Mojgan; Munhoz, Renato P.; et al.
Abstract: Background: Patients with Parkinson's disease might develop treatment‐resistant axial dysfunction after bilateral subthalamic stimulation. Objectives: To study whether lateralized stimulation (unilateral 50% amplitude reduction) for ≥21 days results in ≥0.13 m/s faster gait velocity in the dopaminergic ON state in these patients, and its effects on motor and axial function, quantitative gait and speech measures, quality of life, and selected cognitive tasks. Methods: Randomized, double‐blinded, double‐crossover trial. Results: In 22 participants (51–79 years old, 15 women), there were no significant changes in gait velocity, quality of life, cognitive, and speech measures. Reducing left‐sided amplitude resulted in a 2.5‐point improvement in axial motor Movement Disorder Society Unified Parkinson's Disease Rating Scale (MDS‐UPDRS) ( P = 0.005, uncorrected) and a 1.9‐point improvement in the Freezing of Gait Questionnaire ( P = 0.024, uncorrected). Conclusions: Lateralized subthalamic stimulation does not result in meaningful improvement in gait velocity in patients with Parkinson's disease who develop treatment‐resistant axial dysfunction after bilateral subthalamic stimulation. Left subthalamic overstimulation may contribute to axial deterioration in these patients. © 2022 International Parkinson and Movement Disorder Society